Effect of subtle neurological dysfunction on response to haloperidol treatment in schizophrenia - Convit, A; Volavka, J; Czobor, P; de Asis, J; Evangelista, C (The American journal of psychiatry, 1994)
The primary purpose of this study was to assess whether an interaction between subtle neurological impairment and haloperidol plasma level affects treatment response and, if so, the impact on negative symptoms in particular. Forty-three schizophrenic and two schizoaffective inpatients diagnosed according to Research Diagnostic Criteria were given, at the end of a 1-week placebo period, a baseline evaluation consisting of the Brief Psychiatric Rating Scale (BPRS), Scales for the Assessment of Positive and Negative Symptoms, Quantified Neurological Scale, and the Simpson-Angus Scale for extrapyramidal side effects. Subjects were randomly assigned to one of three haloperidol plasma ranges and treated for 6 weeks. At the end point the BPRS, Scales for the Assessment of Positive and Negative Symptoms, and Simpson-Angus Scale were readministered. Multiple linear regressions were used to assess the extent to which the interaction between neurological abnormality and haloperidol plasma level predicted the end-point symptoms once the baseline symptoms, neurological abnormality, and haloperidol plasma level were accounted for. Those patients with higher levels of overall abnormality on the Quantified Neurological Scale at baseline and with frontal dysfunction in particular, had, with increasing haloperidol plasma levels, more severe negative symptoms at end point. Neurological dysfunction was not related to end-point positive symptoms. The effect was specific to end-point negative symptoms and was independent of extrapyramidal side effects. If confirmed, these findings may indicate that relatively intact frontal function is needed for improvement in negative symptoms and that those patients with schizophrenia who have subtle neurological dysfunction should be treated with lower doses of neuroleptics.